Potential international crimes in Ukraine: should atrocities in Bucha be classified as genocide, war crimes, or crimes against humanity? - D. L. R. Tchobo (Law and Safety)
The dilemma between the root of the word Genocide and its legal meaning is affecting the international criminal justice system. The proof is that Presidents Volodymyr Zelenskyy of Ukraine and Joe Biden of the USA called the atrocity crimes observed in Ukraine “Genocide”. The purpose of this study is to examine whether the atrocities that recently occurred in Bucha could be qualified as a crime of genocide. This article substantially analyzed the meaning of the terms composing the word genocide in the context of the nature of those atrocity crimes. In this regard, it was found that there is etymologically a gap between the legal meaning of genocide and the nature of the crime in question which shields its alleged perpetrators from impunity. Thus, this paper attempted to demonstrate that the alleged atrocity crimes observed in Bucha could not be classified as genocide and then, exposed the potential international crimes committed in Ukraine.